PENGARUH DETERMINAN KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER DI INDONESIA - Tiara Rose; Sufiyati Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This research was conducted with the aim of obtaining empirical evidence regarding the effect of debt to equity ratio (DER), current ratio (CR), total asset turnover (TATO), firm size (SIZE), and cash turnover (CTO) on return on assets (ROA) for primary consumer goods sector companies listed on the Indonesia Stock Exchange in 2019-2021. The selection of samples using purposive sampling method and valid data is 29 companies. Data processing in this study used multiple regression analysis techniques with the Eviews software program version 12.0 and Microsoft Excel 2013. The results obtained showed that DER and TATO had a significant effect on ROA, but CR, SIZE, and CTO had no significant effect on ROA. The implication of this research is the need to carry out evaluations that are useful in making decisions in an effort to improve the company's financial performance which will provide a good signal for investors.